Impact of the gut microbiome on skin fibrosis: a Mendelian randomization study - Zhao, Zirui; Xu, Zhongye; Lv, Dongming; Rong, Yanchao; Hu, Zhicheng; Yin, Rong; Dong, Yunxian; Cao, Xiaoling; Tang, Bing (Frontiers in Medicine, 2024)
Objective Skin fibrosis is a lesion in the dermis causing to itching, pain, and psychological stress. The gut microbiome plays as an essential role in skin diseases developments. We conducted a Mendelian randomization study to determine the causal association between the gut microbiome and skin fibrosis. Methods We retrieved valid instrumental variables from the genome-wide association study (GWAS) files of the gut microbiome (n = 18340) conducted by the MiBioGen consortium. Skin fibrosis-associated data were downloaded from the GWAS Catalog. Subsequently, a two-sample Mendelian randomization (MR) analysis was performed to determine whether the gut microbiome was related to skin fibrosis. A reverse MR analysis was also performed on the bacterial traits which were causally associated with skin fibrosis in the forward MR analysis. In addition, we performed an MR-Pleiotropy Residual Sum and Outlier analysis to remove outliers and a sensitivity analysis to verify our results. Results According to the inverse variance-weighted estimation, we identified that ten bacterial traits (Class Actinobacteria, Class Bacteroidia, family Bifidobacteriaceae, family Rikenellaceae, genus Lachnospiraceae (UCG004 group), genus Ruminococcaceae (UCG013 group), order Bacteroidales, order Bifidobacteriales, genus Peptococcus and genus Victivallis) were negatively correlated with skin fibrosis while five bacterial traits (genus Olsenella, genus Oscillospira, genus Turicibacter, genus Lachnospiraceae (NK4A136group), and genus Sellimonas) were positively correlated. No results were obtained from reverse MR analysis. No significant heterogeneity or horizontal pleiotropy was observed in MR analysis. Objective Conclusion There is a causal association between the gut microbiome and skin fibrosis, indicating the existence of a gut–skin axis. This provides a new breakthrough point for mechanistic and clinical studies of skin fibrosis.